Randomized Controlled Trial of Point-of-Care Ultrasound Education for the Recognition of Tension Pneumothorax by Paramedics in Prehospital Simulation. Issue 1 (17th February 2021) - Khalil, Paul A.; Merelman, Andrew; Riccio, John; Peterson, Jodi; Shelton, Ryan; Meyers, Jeff; Ketchmark, Tim; Garneau, Emily; Khalil, Stephanie; Roosevelt, Genie; Toney, Amanda
Abstract: Objective: The primary goal of this study was to determine if ultrasound (US) use after brief point-of-care ultrasound (POCUS) training on cardiac and lung exams would result in more paramedics correctly identifying a tension pneumothorax (TPTX) during a simulation scenario. Methods: A randomized controlled, simulation-based trial of POCUS lung exam education investigating the ability of paramedics to correctly diagnose TPTX was performed. The US intervention group received a 30-minute cardiac and lung POCUS lecture followed by hands-on US training. The control group did not receive any POCUS training. Both groups participated in two scenarios: right unilateral TPTX and undifferentiated shock (no TPTX). In both scenarios, the patient continued to be hypoxemic after verified intubation with pulse oximetry of 86%-88% and hypotensive with a blood pressure of 70/50. Sirens were played at 65 decibels to mimic prehospital transport conditions. A simulation educator stated aloud the time diagnoses were made and procedures performed, which were recorded by the study investigator. Paramedics completed a pre-survey and post-survey. Results: Thirty paramedics were randomized to the control group; 30 paramedics were randomized to the US intervention group. Most paramedics had not received prior US training, had not previously performed a POCUS exam, and were uncomfortable with POCUS. Point-of-care US use was significantly higher in the US intervention group for both simulation cases (P <.001). A higher percentage of paramedics in the US intervention group arrived at the correct diagnosis (77%) for the TPTX case as compared to the control group (57%), although this difference was not significantly different (P = 0.1). There was no difference in the correct diagnosis between the control and US intervention groups for the undifferentiated shock case. On the post-survey, more paramedics in the US intervention group were comfortable with POCUS for evaluation of the lung and comfortable decompressing TPTX using POCUS (P <.001). Paramedics reported POCUS was within their scope of practice. Conclusions: Despite being novice POCUS users, the paramedics were more likely to correctly diagnose TPTX during simulation after a brief POCUS educational intervention. However, this difference was not statistically significant. Paramedics were comfortable using POCUS and felt its use improved their TPTX diagnostic skills.